Teaching Speaking Strategy Used by Lecturer at Public Speaking Class in IAIN Palangka Raya - Soraya, Rika; Asi, Natalina; Bahing, Bahing (IKIP Siliwangi, 2025)
A teaching strategy uses methods to achieve specific goals. To improve students' speaking skills, new strategies like discussion and debate are needed. The goal of the study was to determine how the lecturer used these strategies, what challenges the students and the lecturer encountered, and how the strategies used to teach public speaking at IAIN Palangka Raya affected the students. The study design employed by the researcher was a case study and the qualitative method. Three instruments were utilized observation, interview, and documentation for collecting the data. The subject was a lecturer and the students 4th semester of English education in public speaking at IAIN Palangka Raya. The researcher obtained the lecturer used discussion and debate. Those strategies were used alternately in each meeting in public speaking class. Before meeting, the students had got the topic from the lecturer and the students should prepare their ideas to show in front of their friends and lecturers. Three problems that the researcher found, there were linguistic factors, psychological factors, and external factors. The students also had improvement in several things such as speaking elements, motivation, and self-confidence.